PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING BERBASIS SOAL HOTS PADA MATERI SPLTV DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XF SMA NEGERI 2 ABIANSEMAL TAHUN PELAJARAN 2023/2024 - I Made Surat; I Wayan Edi Ari Suandana; Ika Desi Budiarti (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Abstrak Problem solving is the process of identifying, analyzing, and resolving a problem through systematic and creative steps to achieve the desired goal or solution. High Order Thinking Skills (HOTS) questions are educational assessments that test higher-order thinking abilities. The purpose of this research is to determine the response and whether the implementation of the problem-solving learning model can enhance students' ability to answer HOTS questions on SPLTV material. The research subjects are students of class XF at SMA Negeri 2 Abiansemal for the academic year 2023/2024. The study focuses on understanding SPLTV material with an orientation towards HOTS questions and students' responses to the problem-solving learning model. This research employs a classroom action research design, consisting of two cycles with four stages of activity processes, including (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection involves assessing student test results as quantitative data and using observation techniques for qualitative data. The research findings indicate that (1) the implementation of the problem-solving learning model can improve students' ability to answer HOTS questions on SPLTV material, and (2) there is a positive response from students towards the implementation of the problem-solving learning model to enhance their ability to answer HOTS questions on SPLTV material